2014
DOI: 10.14330/jeail.2014.7.2.06
|View full text |Cite
|
Sign up to set email alerts
|

International Arbitration of Maritime Delimitation: An Alternative for East Asia?

Abstract: International arbitration, as a neutral, flexible, efficient and binding legal means of dispute resolution, has been effective in settling maritime delimitation disputes, especially in recent years since the UNCLOS came into force. There are a number of reasons (i.e. advantages) for its increased popularity. Reasonable expectations thus arise as to its applicability onto similar maritime delimitation disputes of the East Asian countries whose diplomatic efforts have mostly failed to address these matters. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The investment environment guaranteed by the great ability to enforce arbitration awards is conducive to attracting foreign investors and FDI. 4 The study of Wagle (2011) demonstrates a positive association between the quality of arbitration and FDI. In Myburgh and Paniagua's (2016) research, international arbitration was found to have a positive impact on FDI, showing that countries' accession to the New York Convention has a beneficial effect on the rise in the level of bilateral FDI.…”
Section: International Arbitration Can Promote Fdi Which Contributes ...mentioning
confidence: 99%
“…The investment environment guaranteed by the great ability to enforce arbitration awards is conducive to attracting foreign investors and FDI. 4 The study of Wagle (2011) demonstrates a positive association between the quality of arbitration and FDI. In Myburgh and Paniagua's (2016) research, international arbitration was found to have a positive impact on FDI, showing that countries' accession to the New York Convention has a beneficial effect on the rise in the level of bilateral FDI.…”
Section: International Arbitration Can Promote Fdi Which Contributes ...mentioning
confidence: 99%